Sistem Informasi Geografis Pemetaan Wedding Vendor Berbasis Website (Studi Kasus : Kabupaten Timor Tengah Utara) - Maria Sisilia Luruk Nahak; Yoseph Pius Kurniawan Kelen; Anastasia Kadek Dety Lestari (Program Studi Teknik Informatika Universitas Nusa Putra, 2023)
The growth of information technology (IT) and science in the era of globalization has collaborated with many other fields of science and entered all fields. This resulted in the use of information technology is needed to achieve certain goals of an organization. In the business world, advances in information technology can make it easier for entrepreneurs to run their businesses, which were initially managed manually, now can be managed with a geographic information system. Marriage is a form of human relationship carried out by two people who formalize a sacred promise bond. In the process of getting married, it takes a mature preparation. Photography, decorations, invitations, sound systems, gold shops (wedding rings) and bridal make up are the six main things that are often used in weddings. The process of searching for these six things is still very manual, such as the bride and groom must first come to the photo studio, decoration rental, invitation printer, sound system renter, gold (wedding ring) shop and bridal make up to find out what is offered and in detail. so we need a geographic information system that can map wedding vendors in North Central Timor District.